Response Surface Method-driven Design of Experiments for The Sublingual Immunotherapy Tablets of Indonesian House Dust Mites Allergenic Extract - Yusuf Alif Pratama; Honey Dzikri Marhaeny; I Made Slamet Putra Prasetya; Anak Agung Istri Evinia Pramesthi; Sulistyanengci Winarto; Andang Miatmoko; Chrismawan Ardianto; Mahardian Rahmadi; Muhammad Taher; Junaidi Khotib (Universitas Airlangga, 2026)
Background: Allergic diseases represent a significant global health burden, and current pharmacological treatments primarily offer symptomatic relief without addressing the underlying immune dysregulation. Allergen-specific immunotherapy (AIT) is the only disease-modifying approach capable of inducing long-term remission by targeting the immunological mechanisms that drive the allergic response. Sublingual immunotherapy (SLIT) is a noninvasive alternative to subcutaneous immunotherapy, leveraging the rich vascularisation and antigen-presenting cell population of the oral mucosa. Objective: SLIT tablets were formulated using Indonesian house dust mite (IHDM) allergenic extracts, with the aim of optimising tablet properties by modulating the disintegrant concentration and croscarmellose-to-crospovidone ratios. Methods: Six formulations, each with three batches, were prepared via direct compression, varying the total disintegrant content (5.25 and 10.5% w/w) and excipient ratios. The tablets were evaluated for hardness, disintegration time, friability, and dissolution, and specific allergenic protein release (Der p 1 as a marker) was quantified using ELISA. A 2 × 3 factorial experimental design was used in the DoE approach, with data analysed using GraphPad Prism and Minitab, and response surface methodology (RSM) applied via Stat-Ease 360. Results: Higher disintegrant concentrations reduced tablet hardness but increased friability and disintegration rates. Pareto analysis revealed that both the total disintegrant content and disintegrant ratio significantly influenced tablet performance. All formulations demonstrated favourable dissolution profiles. The optimised formulation (F2), containing 5.25% (w/w) total disintegrants with a croscarmellose-to-crospovidone ratio of 1.5:2, achieved a disintegration time of 4.33 ± 0.88 s, hardness of 89.20 ± 6.12 N, and friability of 0.00 ± 0.01 %. Conclusion: These findings support the potential of IHDM-based SLIT tablets as an effective and mechanistically rational platform for allergen immunotherapy, contributing not only to symptoms but also to long-term modification of allergic diseases